Application of Guided Reading Method in Improving Students' Reading Comprehension Skills in Grade IV of SDN 1 Anyar - Neta Karlina; Raden Sumiadi; Fitriani Rahayu (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The aim of this research is to improve students' reading comprehension skills by using the guided reading method in grade IV students of SDN 1 Anyar, North Lombok Regency. This research is qualitative research with a classroom action approach (CAR), which consists of 4 stages, namely planning, implementation, observation and reflection. This research was conducted in the fourth grade of SDN 1 Anyar, Bayan District, North Lombok Regency, with 28 fourth grade students as subjects. To obtain valid data, the data collection instruments used were observation guidelines, interview guidelines, documentation, and reading comprehension tests. Data collection techniques were carried out through activity of observation, interviews, documentation, and tests. Data analysis techniques used descriptive statistics. The results of the study indicate that there was an increase in the reading comprehension skills of fourth-grade students at SD Negeri 1 Anyar using the guided reading method which can be seen from the percentage of students who completed in cycle I 57.14% and in cycle II the percentage of students who completed 82.14%, thus increasing by 25%.